The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10554-015-0749-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on aortic root growth rate in patients with bicuspid aortic valve anatomy

Abstract: Bicuspid aortic valve (BAV) anatomy is associated with increased growth rate of the aortic root compared to tricuspid aortic valves. Statins decrease the growth rate of abdominal aneurysms; however their effect on the aortic root growth rate has not been elucidated. The present study evaluated the association between use of statins and aortic root growth in patients with BAV. A total of 199 patients (43 ± 15 years, 69 % male) with BAV who underwent ≥2 echocardiographic measurements of the aortic root ≥1 year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Recently, statins have been found to exert biological effects on osteoporosis, inflammation and other diseases in addition to their hypocholesterolemic activities [29][30][31]. Furthermore, several studies have shown that treatment with statins can reduce reproductive damage induced by hypercholesterolemia, however, the mechanisms by which obesity impairs spermatogenic function and how statins help recover from obesity-induced damage in the testes, sperm parameters, sex hormones, and metabolism is still unclear [32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, statins have been found to exert biological effects on osteoporosis, inflammation and other diseases in addition to their hypocholesterolemic activities [29][30][31]. Furthermore, several studies have shown that treatment with statins can reduce reproductive damage induced by hypercholesterolemia, however, the mechanisms by which obesity impairs spermatogenic function and how statins help recover from obesity-induced damage in the testes, sperm parameters, sex hormones, and metabolism is still unclear [32].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with BAV aortopathy, medical management with b-blockers, angiotensin converting enzyme inhibitors, or statins has not been proven to be effective. [111][112][113] The optimal timing for surgical aortic replacement is controversial. An ascending aorta measuring 50 mm at its widest diameter had previously been cited to be an indication for surgery.…”
Section: Recommendations For Interventionmentioning
confidence: 99%
“…Statins have been shown to be ineffective, whereas other studies show a possible protective effect. 55…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%